1995
DOI: 10.1161/01.cir.92.12.3431
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Endothelium-Dependent Flow-Mediated Dilatation of the Brachial Artery by Sex and Menstrual Cycle

Abstract: Endothelium-dependent vasodilatation varies during the menstrual cycle. The endogenous estradiol may be involved in this menstrual cycle-related vasodilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
323
5
14

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 495 publications
(378 citation statements)
references
References 27 publications
36
323
5
14
Order By: Relevance
“…Moreover, only male medical personnel were included in this study because menstrual cycle in women might have influenced the results of FMD measurements. 26,27 Further investigation was necessary to clarify whether similar results were observed in women. In addition, this study was focused on the short-term effect of aromatherapy on endothelial dysfunction after night-shift work.…”
Section: Study Limitationsmentioning
confidence: 90%
“…Moreover, only male medical personnel were included in this study because menstrual cycle in women might have influenced the results of FMD measurements. 26,27 Further investigation was necessary to clarify whether similar results were observed in women. In addition, this study was focused on the short-term effect of aromatherapy on endothelial dysfunction after night-shift work.…”
Section: Study Limitationsmentioning
confidence: 90%
“…22,26,27 The variability of the ultrasound measurements was studied for both %FMD and %NTG by repeated measurements from the same video recordings in six subjects. 23 The Flow-mediated vasodilatation in obesity M Hashimoto et al coefÂźcient of variation for measurements of %FMD was 5.84 AE 0.25%. The coefÂźcient of variation for measurements of %NTG was 3.97 AE 0.24%.…”
Section: Methodsmentioning
confidence: 99%
“…25 Maximal vasodilatation was observed 45±60 s after the cuff release. 21,23 The diameter change, caused byÂŻow-mediated vasodilatation, was expressed as the percent change relative to that at the initial resting scan (%FMD). The diameter change caused by NTG was expressed in the same way as the percent change relative to that at the recovery scan (%NTG).…”
Section: Methodsmentioning
confidence: 99%
“…18,19 Direct vascular action of estrogen Two estrogen receptor (ER) subtypes, ERa and ERb, have been identified and are expressed in the vasculature, and experimental studies have demonstrated the vasodilator effects of estrogen/ER through their action on the endothelium, smooth muscle and extracellular matrix. Estrogen enhances endothelium-dependent vasorelaxation via increased release of nitric oxide (NO), [20][21][22] endothelium-derived hyperpolarizing factor 23 and PGI 2 24,25 and decreased production of endothelin-1 (Table 1). 26 Several studies have demon-strated that estrogen inhibits calcium influx 27,28 and stimulates calcium efflux 29 in vascular smooth muscle cells (VSMCs), leading to endothelium-independent vasodilation.…”
Section: Action Of Estrogen On the Cardiovascular Systemmentioning
confidence: 99%